Crack Propagation Simulation Using Ansys For Bamboo Composites - Abd Jalil, Muhammad Faris Fauzan; mohamad, zaleha (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Nowadays, natural fibre composite was suggested to replace the existing composite materials in the manufacturing sector. This is because natural fibre composite is more sustainability and environmental-friendliness than another composite material. Therefore, bamboo was selected as a natural fibre composite. This is because bamboo is one of the most readily available crops, lightweight and has a low cost compared to existing composite materials. Moso bamboo and Guadua bamboo has been choose to running the simulation using Ansys Workbench R3 software. Moso bamboo can be found in China and the most widely used bamboo species in the world for industrial bamboo production. While Gudua bamboo can be found in South America’s and the most important bamboo on this continent. These two bamboos are among the most important bamboos in the world because they are among the main suppliers in the world’s bamboo industry sector. In this experiment, the analysis for crack propagation has been done. The numerical simulation for both bamboos has been done by using quasi static loading method. This experiment focuses on the different type of specimen of bamboo composite which is rectangular path with right crack, rectangular part with left crack, beam under four-point bending and crack with one hole. In this experiment, the analysis has been done for independent cracking mode for mode l, only. The relationship between stress intensity factor and length of crack and relationship between crack extension and time for five second after crack propagation process had been discuss for this experiment. The forces that been applied to cracking surface on every specimen is different because the types of notch pattern from crack initiation are also different. The different types of shaped of specimens produce different types of results from this experiment.